Multifocal Oral Epstein–Barr Virus-Positive Mucocutaneous Ulcers Associated with Dual Methotrexate and Leflunomide Therapy: A Case Report - Kunmongkolwut, Sumana; Amornkarnjanawat, Chatchawan; Phattarataratip, Ekarat (European Journal of Dentistry, 2022)
Epstein–Barr virus (EBV)-positive mucocutaneous ulcer (EBVMCU) is a unique clinicopathologic entity of lymphoproliferative disorder, occurring in immunosuppressed patients. Due to its rarity, EBVMCU may be under-recognized by clinicians as well as pathologists. In addition, its clinical and histopathologic features overlap with other benign and malignant conditions, making a diagnosis challenging. This report presents an unusual case of multifocal oral EBVMCUs in a 52-year-old female patient with rheumatoid arthritis, receiving the combination of methotrexate and leflunomide for 5 years. The patient presented with persistent multiple large painful ulcers involving her palate and gingiva for 6 months. The histopathologic examination revealed extensive ulceration with diffuse polymorphic inflammatory infiltrate admixed with scattered atypical lymphoid cells showing occasional Hodgkin and Reed/Sternberg-like cell features. These atypical cells showed immunoreactivity for CD20, CD30 and MUM1/IRF4. EBV-encoded small RNA in situ hybridization was positive, validating the presence of EBV-infected cells. Two months after discontinuation of both immunosuppressive medications, oral lesions gradually regressed. At 9-month follow-up, no evidence of relapsing oral EBVMCU has been observed. The multifocal presentation of EBVMCU is rare and could be resulted from the overwhelming immune suppression by long-term use of dual immunosuppressants. Its diagnosis requires comprehensive correlation of patient history, clinical findings, histopathologic, and immunophenotypic features. The ability of EBVMCU to regress following removal of immunosuppressive causes is in drastic contrast to a variety of its potential clinical and histopathologic mimics. Therefore, accurate diagnosis is crucial to avoid unnecessary patient management and achieve optimal patient outcomes.
Keywords: Epstein–Barr virus infections; leflunomide; lymphoproliferative disorders; methotrexate; oral ulcerations